Associations Between Negative Symptoms and Effort Discounting in Patients With Schizophrenia and Major Depressive Disorder. Issue 1 (11th June 2021) - Cathomas, Flurin; Klaus, Federica; Guetter, Karoline; Seifritz, Erich; Hartmann-Riemer, Matthias N; Tobler, Philippe N; Kaiser, Stefan; Kaliuzhna, Mariia
Abstract: Deficits in goal-directed decision making and motivation are hallmark characteristics of several neuropsychiatric disorders, including schizophrenia (SZ) and major depressive disorder (MDD). Studies using effort-based decision-making tasks have shown that both patients with SZ and MDD invest less physical effort in order to obtain rewards. However, how these motivational deficits relate to clinically assessed symptom dimensions such as apathy remains controversial. Using a grip-strength-based effort discounting task we assessed effort-based decision-making behavior in healthy controls (HC) ( N = 18), patients with SZ ( N = 42), and MDD ( N = 44). We then investigated how effort discounting relates to different symptom dimensions. There were no differences in effort discounting between HC participants and patients with SZ or MDD. In addition, we did not observe a correlation between effort discounting and negative symptoms (NS) in patients with SZ or MDD. In conclusion, the current study does not support an association between effort discounting and NS in SZ or MDD. Further studies are needed to investigate effort discounting and its relation to psychopathological dimensions across different neuropsychiatric disorders.